Mass reproduction of previously identified trichodermas fungi from Nicaraguan soils in different organic substrates - López Martínez, Tatiana de los Ángeles; Páramo Aguilera, Leandro Alberto; Delgado Silva, Heysell Dodanig (Nexo Revista Científica, 2022)
Trichodermas mushrooms are of vital importance to keep plant crops free of phytopathogenic fungi, so the present research consisted of finding the best organic substrate for the mass reproduction of Trichodermas fungi, previously identified from Nicaraguan soils. Substrates were used such as Rice in the control, Corn, Corn cob, Coconut Copra and Molasses as a supplement to the before mentioned substrates, with 5 strains, previously identified as Trichoderma harzianum (72TG-11), Trichoderma harzianum (T3), Trichoderma harzianum (CVD-06), Trichoderma sp. (CIXD-11) y Trichoderma longibrachiatum (QIVD-12). Through solid and biphasic fermentation, the spore production process was carried out for 26 and 15 days, respectively; obtaining as a result that the corn cob substrate yielded spore concentration very close to those obtained with the rice substrate. With molasses addition to the different substrates, a slight increase of the concentration spores compared to those obtained in substrates without molasses was obtained, except with the strains T3 and CVD-06, where apparently there aren´t appreciable difference in the number of spores obtained. In the other hand, corn cob substrate is the best substrate for mass reproduction of Trichodermas fungi, since satisfactory results are obtained in both fermentations and there aren´t competition with human being food.